2017
DOI: 10.1021/jacs.7b09967
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Screening of Hemagglutinin on Influenza A Virus Particles: Sialyl-LacNAc Displays on DNA and PEG Scaffolds Reveal the Requirements for Bivalency Enhanced Interactions with Weak Monovalent Binders

Abstract: Attachment of the Influenza A virus onto host cells involves multivalent interactions between virus surface hemagglutinin (HA) and sialoside-containing glyco ligands. Despite the development of extremely powerful multivalent binders of the Influenza virus and other viruses, comparably little is known about the optimal spacing of HA ligands, which ought to bridge binding sites within or across the trimeric HA molecules. To explore the criteria for ligand economical high affinity binding, we systematically probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 57 publications
3
94
0
Order By: Relevance
“…The inhibitory constants of virusinduced hemagglutination (KHAIi ) improved 10 4 ‐fold upon trivalent presentation of sialyl‐lactose ligands. We used DNA‐programmed spatial screening to identify the optimal arrangement of sialyl‐LacNAc displays and showed that 1.360‐fold enhancements over monovalent binding can be achieved with only two sugar ligands, provided that the sugars are arranged at the 52–59 Å distance necessary to bind two of the three binding sites within a HA trimer simultaneously (Figure B) . Note, we also obtained the first evidence for target specificity: an optimized intratrimeric, bivalent HA binder inhibited hemagglutination induced by an H3N2 influenza A virus (IAV) ten times better than that by an H1N1 IAV.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory constants of virusinduced hemagglutination (KHAIi ) improved 10 4 ‐fold upon trivalent presentation of sialyl‐lactose ligands. We used DNA‐programmed spatial screening to identify the optimal arrangement of sialyl‐LacNAc displays and showed that 1.360‐fold enhancements over monovalent binding can be achieved with only two sugar ligands, provided that the sugars are arranged at the 52–59 Å distance necessary to bind two of the three binding sites within a HA trimer simultaneously (Figure B) . Note, we also obtained the first evidence for target specificity: an optimized intratrimeric, bivalent HA binder inhibited hemagglutination induced by an H3N2 influenza A virus (IAV) ten times better than that by an H1N1 IAV.…”
Section: Figurementioning
confidence: 99%
“…The sequence design of the shorter tandem DNA (39 nt) was chosen so as to allow the adjacent annealing of three peptide nucleic acid (PNA) 13‐mers, that is, two sugar‐modified α2,6‐sialyl‐LacNAc‐PNA conjugates (PNAs 1 and 2 ) and the unmodified spacer PNA oligomer (PNA 3 ; Figure B). The synthesis of the conjugates was previously reported . Multiple linear hybridization enabled concatenation of sialyl‐LacNAc‐PNA conjugates.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[27] Similar procedures could be implemented for the discovery of reversible covalent binders by incorporating 2-hydroxybenzaldehyde or similar moieties during library construction. [28] It will be interesting to investigate whether more reactive lysine modifiers (or modifiers for other amino acids) can be used for pharmaceutical applications.From athermodynamic viewpoint, practical applications would be limited by the molar concentration of amino acid residues in serum and in tissues.H owever,s ince Schiff-base formation is ar elatively slow reaction, it may be conceivable that a" dock-and-lock" procedure may allow the selective in vivo modification of target proteins,i fk inetic parameters are judiciously chosen. [11,19] Moreover,DNA structures have been used to probe the magnitude of affinity gain by polydentate engagement with multivalent protein target.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It remains unknown which and how many of the several glyco ligands engage on binding and, therefore, these scaffolds do not provide information about the optimal spacing of HA ligands. In order to identify the criteria for enhanced binding at high ligand economy and learn about the arrangement of binding sites on the IAV particle, we used DNA‐programmed bivalent screening . We figured that a range of far reaching scaffolds would be required to assess the potential for enhanced interactions upon bridging of two sugar binding sites within an HA trimer and across HA trimers on the IAV surface (Figure B).…”
Section: Termolecular and Multimolecular Assemblies For Nucleic Acid–mentioning
confidence: 99%